The Impact of Consumers` impressions of Facebook commercial and Advertisement on Their attitudes & purchase Intention A field study addressed at the consumers of ready-made clothes and the flowers of their advertisements via Facebook from private -Univers (Damascus University Journal for the economic and Political sciences, 2021)
Social media, especially Facebook, have become audio-visual advertising tools that affect consumers' response and purchasing intentions. In this research we will focus on Facebook advertisements and the impact of consumer perceptions of the advertisements on the company’s Facebook page on their purchase intentions and the intermediary role of consumers’ trends. A descriptive analytical approach was used in collecting data on consumer social perceptions of Facebook advertisements, company's official page advertisement and the WOM. The study was conducted on a convenience sample of 130 followers of Facebook advertisement from students in private universities and Statistical Analysis of Social Sciences (SPSS.24) was used to analyze consumer responses. simple regression was used to study the effect of independent variables on the dependent variable and the effect of the intermediate variable on the dependent variable and then the multiple regression analysis was used to study the effect of the independent variables together on both the intermediate and the dependent variables. Path analysis using Barron's method was also used to study the effect of both independent and median variables on the dependent variable. The results of the study indicate that the most important consumers impressions about the advertisements of ready-made clothes via Facebook is the social impression, followed by the impression of personal character then followed by the impression of the electronic word of mouth. The study also showed that consumer attitudes play a mediocre role in the relationship between electronic word of mouth impressions and the intention of purchase as well as between social impressions and the intention to buy.
Keywords: Facebook advertisements; Consumers social impressions; Consumers impressions of company official page; electronic word of mouth; Consumer’s attitudes; Purchase intention.